Erythema nodosum manifestation of Parvovirus B19-associated reactive arthritis - Maryam Kareem Ali; Jaafar Sataar Shia (Journal of Infection in Developing Countries)
Introduction: Parvovirus B19 virus-mediated viral inflammation and immune-complex deposition generate mainly short-term manifestations in the affected individuals. The objective of this study was to determine Parvovirus B19 infection in rheumatoid arthritis (RA) patients.